The ASH‐ASPHO Choosing Wisely Campaign: 5 hematologic tests and treatments to question. Issue 8 (28th May 2021) - O'Brien, Sarah H.; Badawy, Sherif M.; Rotz, Seth J.; Shah, Mona D.; Makarski, Julie; Bercovitz, Rachel S.; Hogan, Mary‐Jane S.; Luchtman‐Jones, Lori; Panepinto, Julie A.; Priola, Ginna M.; Witmer, Char M.; Wolfson, Julie A.; et al.
Abstract: Choosing Wisely is a medical stewardship and quality‐improvement initiative led by the American Board of Internal Medicine Foundation in collaboration with leading medical societies in the United States. The American Society of Hematology (ASH) has been an active participant in the Choosing Wisely project. In 2019, ASH and the American Society of Pediatric Hematology/Oncology (ASPHO) formed a joint task force to solicit, evaluate, and select items for a pediatric‐focused Choosing Wisely list. By using an iterative process and an evidence‐based method, the ASH‐ASPHO Task Force identified 5 hematologic tests and treatments that health care providers and patients should question because they are not supported by evidence, and/or they involve risks of medical and financial costs with low likelihood of benefit. The ASH‐ASPHO Choosing Wisely recommendations are as follows: (1) avoid routine preoperative hemostatic testing in an otherwise healthy child with no previous personal or family history of bleeding, (2) avoid platelet transfusion in asymptomatic children with a platelet count 10 × 10 3 /μL unless an invasive procedure is planned, (3) avoid thrombophilia testing in children with venous access‐associated thrombosis and no positive family history, (4) avoid packed red blood cells transfusion for asymptomatic children with iron deficiency anemia and no active bleeding, and (5) avoid routine administration of granulocyte colony‐stimulating factor for prophylaxis of children with asymptomatic autoimmune neutropenia and no history of recurrent or severe infections. We recommend that health care providers carefully consider the anticipated risks and benefits of these identified tests and treatments before performing them.